Factors influencing scattering coefficient measurement accuracy in scaled reverberation room. (February 2020) - Pan, Lili; Zhao, Yuezhe; Gao, Jianliang
Abstract: The method described in ISO 17497-1 standard has been worldwide adopted to measure the random-incident scattering coefficient of irregular surfaces either in a full-size reverberation room or in a scale model. In practical measurements, the sound energy propagation and decay at high frequencies (over 10 kHz) are easily affected by small operating errors and by tiny changes in the measurement conditions. It is difficult to obtain the same accuracy of results in the scale model as that in a full-size reverberation room while maintaining the same setup in both tests as suggested in the standard. This study performed a series of experiments in a 1:10 scale reverberation room to investigate the influence of several practical aspects on measurement accuracy. A maximum length sequence diffuser, with a design frequency of 1700 Hz (full-size value), was used as the specimen. All results obtained in the scaled reverberation room were compared to the reference values measured in a full-size reverberation room. Five factors were studied, which included different recording methods (double-channel and eight-channel), number of source positions (one and four), number of receiver positions (one, two, four and eight), turntable rotation conditions (full-turn or half-turn rotation during T 3 and T 4 measurements), and numbers of averages (24, 36 and 72). The results show that the first three factors above have greater impacts on the measurement accuracy of the scale model experiments than the remaining factors. When the multichannel recording method and four source positions were used in the scaled tests, the measured scattering coefficient values were more reliable, appearing much closer to the reference data over the whole frequency range. Furthermore, applying a half-turn of the turntable (in reference to the measurements of the axisymmetric diffusers) and a 36-impulse coherent average can greatly reduce the test duration without decreasing the measurement accuracy.